An analysis of the girl scouting program in Mandaluyong a basic for development planning - De Jesus, Evangeline M. (1976)
This study analyzed the Girl Scouting Program in Mandaluyong and proposed revisions to integrate the program toward national development goals. The program is weak because of lack of competent leaders. Personnel are almost all volunteers including teachers/leaders who do not possess the necessary training for proper program implementation. Potential leaders are financially handicapped and are unable to attend training. Membership is very low.
Includes tables and appendices
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: Girl scouts